Convention on the Settlement of Investment Disputes between States and Nationals of Other States (The ICSID Convention, 1965) - O. S. Shaposhnikova (Московский журнал международного права, 2012)
The article generally reviews the Convention on the Settlement of Investment Disputes between States and Nationals of Other States (The ICSID Convention), 1965, according to which the International Centre for Settlement of Investment Disputes (ICSID) was established.Nevertheless the ICSID Convention is of framework character and in the Preamble to the Convention, it is mentioned that no Contracting Party shall by the mere fact of its ratification, acceptance or approval of this Convention and without its consent be deemed to be under any obligation to submit any particular dispute to conciliation or arbitration, detailed research of the ICSID Convention key statements is of great importance as it allows to clarify the mechanism of international investment arbitration as well as its distinguishing features.In conclusion of the article, the new international projects similar to the ICSID Convention are mentioned.